Site-directed cross-linking of mRNA analogues to 16S ribosomal RNA; a complete scan of cross-links from all positions between '+1' and '+16' on the mRNA, downstream from the decoding site. - Rinke-Appel, J (1993)
mRNA analogues containing 4-thiouridine residues at selected sites were used to extend our analysis of photo-induced cross-links between mRNA and 16S RNA to cover the entire downstream range between positions +1 and +16 on the mRNA (position +1 is the 5'-base of the P-site codon). No tRNA-dependent cross-links were observed from positions +1, +2, +3 or +5. Position +4 on the mRNA was cross-linked in a tRNA-dependent manner to 16S RNA at a site between nucleotides ca 1402-1415 (most probably to the modified residue 1402), and this was absolutely specific for the +4 position. Similarly, the previously observed cross-link to nucleotide 1052 was absolutely specific for the +6 position. The previously observed cross-links from +7 to nucleotide 1395 and from +11 to 532 were however seen to a lesser extent with certain types of mRNA sequence from neighbouring positions (+6 to +10, and +10 to +13, respectively); no tRNA-dependent cross-links to other sites on 16S RNA were found from these positions, and no cross-linking was seen from positions +14 to +16. In each case the effect of a second cognate tRNA (at the ribosomal A-site) on the level of cross-linking was studied, and the specificity of each cross-link was confirmed by translocation experiments with elongation factor G, using appropriate mRNA analogues.